The coupling effect of socio-economic and eco-environment and land use transformation in mountainous areas—a case of the Fengjie County in the Three Gorges Reservoir Area, China - Chunhua Xia; Yangbing Li; Jingan Shao; Shijie Yan; Yan Chen; Luoshan Zheng; Rong Wang (Environmental Science and Pollution Research, 2022)

Marine Radar Oil Spill Extraction Based on Texture Features and BP Neural Network - Rong Chen; Baozhu Jia; Long Ma; Jin Xu; Bo Li; Haixia Wang (Journal of Marine Science and Engineering, 2022)
Marine oil spills are one of the major threats to marine ecological safety, and the rapid identification of oil films is of great significance to the emergency response. Marine radar can provide data for marine oil spill detection; however, to date, it has not been commonly reported. Traditional marine radar oil spill research is mostly based on grayscale segmentation, and its accuracy depends entirely on the selection of the threshold. With the development of algorithm technology, marine radar oil spill extraction has gradually come to focus on artificial intelligence, and the study of oil spills based on machine learning has begun to develop. Based on X-band marine radar images collected from the Dalian 716 incident, this study used image texture features, the BP neural network classifier, and threshold segmentation for oil spill extraction. Firstly, the original image was pre-processed, to eliminate co-channel interference noise. Secondly, texture features were extracted and analyzed by the gray-level co-occurrence matrix (GLCM) and principal component analysis (PCA); then, the BP neural work was used to obtain the effective wave region. Finally, threshold segmentation was performed, to extract the marine oil slicks. The constructed BP neural network could achieve 93.75% classification accuracy, with the oil film remaining intact and the segmentation range being small; the extraction results were almost free of false positive targets, and the actual area of the oil film was calculated to be 42,629.12 m2. The method proposed in this paper can provide a reference for real-time monitoring of oil spill incidents.

Copper Toxicity Differentially Regulates the Seedling Growth, Copper Distribution, and Photosynthetic Performance of Citrus sinensis and Citrus grandis - Xin-yu Li; Mei-lan Lin; Ping-ping Hu; Ning-wei Lai; Zeng-rong Huang; Li-song Chen (Journal of Plant Growth Regulation, 2022)

Improved lithium-ion batteries with coral-like anodes made of recycled spherical porous silicon coated with nitrogen-doped carbon - Zhao Zhang; Fengshuo Xi; Xiuhua Chen; Shaoyuan Li; Wenhui Ma; Zhao Ding; Tao Qu; Yongnian Dai; Rong Deng (Environmental Chemistry Letters, 2022)

Study on the Relationship Between Diet, Physical Health and Gut Microflora of Chinese College Students - Xiafen Hu; Jiaqi Guo; Jiadun Wang; Wanxin Liu; Xiaochen Xiang; Siyang Chen; Xinquan Li; Jinhan Tang; Wei Zhang; Hui Chen; Rong Shu; Qingming Wu; et al. (Current Microbiology, 2022)

Characteristics of antibiotic resistance gene distribution in rainfall runoff and combined sewer overflow - Xin-rong Pan; Lei Chen; Li-ping Zhang; Jian-e Zuo (Environmental Science and Pollution Research, 2022)

Genetic characteristics of human coronavirus HKU1 in mainland China during 2018 - Xiangpeng Chen; Yun Zhu; Qi Li; Gen Lu; Changchong Li; Rong Jin; Lei Li; Baoping Xu; Liwei Gao; Ju Yin; Zhengde Xie (Archives of Virology, 2022)

Induced mutation in ELONGATED HYPOCOTYL5 abolishes anthocyanin accumulation in the hypocotyl of pepper - Rong Chen; Can Yang; Hu Gao; Chunmei Shi; Zhiying Zhang; Guangyu Lu; Xinyan Shen; Yaping Tang; Feng Li; Yongen Lu; Bo Ouyang (Theoretical and Applied Genetics, 2022)

Changes in amino acid and fatty acid composition during early development in cobia (Rachycentron canadum) - Jian-sheng Huang; Rong-xin Li; Rui-tao Xie; You-ming Chen; Jian-dong Zhang; Eric Amenyogbe; Gang Chen (Frontiers in Marine Science, 2022)
An estimation of the utilization of endogenous nutrients from the yolk sac that occurs during embryonic and early larval development can be a valuable approach to studying the nutritional requirements of fish larvae. In this study, fertilized eggs, embryos (before the membrane, 24 hours after fertilization), newly-hatched larvae (0-d-old), and open-mouthed larvae (3-day-old, unfed rotifers) samples of cobia ( Rachycentron canadum ) were collected to determine the amino acid and fatty acid profiles. Crude protein composition varies significantly for cobia during the different stages of development. The total amino acids, except for lysine(Lys), histidine (His), methionine(Met), serine(Ser), and glycine(Gly), had no significant change in the early development stage ( P > 0.05); the content of other six essential amino acids (EAA) and six non-essential amino acids (NEAA) was consistent with the changing trend of total essential amino acid. From hatching newly hatched larvae to open-mouthed larvae, except for Leu, Phe and Ser, decreased significantly ( P <0.05). From the utilization rate of FAA, the utilization rate of Lys and Leu was the highest (60.26%) and (52.21%) in the embryonic and endogenous nutritional stages, respectively. The water content of the open-mouthed larvae of cobia was significantly higher than that of the fertilized eggs, embryos, and newly hatched larvae ( P < 0.05). Three kinds of saturated fatty acids (SFA), five kinds of monounsaturated fatty acids (MUFA), and eight kinds of polyunsaturated fatty acids (PUFA) were detected in the dry samples of each developmental stage. Based on these results, juvenile cobia can thrive with a wide range of crude protein concentrations. Further refinement of commercial cobia production feeds would have beneficial consequences for economic and environmental concerns due to the positive impacts of optimizing the protein component as well as the ability to maintain the rapid growth rates. The results show that the larval development of cobia needs to consume large amounts of n3PUFA (especially DHA and EPA) to improve the larvae’s survival rate. Research methods will always have limitations when evaluating the relationship between early life nutrition interventions and well-being outcomes later in life. This study provides essential information regarding cobia larvae’s fatty acid requirements.

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Development of Physiology Based Pharmacokinetic Model to Predict the Drug Interactions of Voriconazole and Venetoclax - Ji Dong; Shuai-bing Liu; Jony Md Rasheduzzaman; Chen-rong Huang; Li-yan Miao (Pharmaceutical Research, 2022)

Fbxw17 is dispensable for viability and fertility in mice - Zhen Chen; Dupeng Ma; Tingyu Jin; Ziqi Yu; Jiong Li; Qi Sun; Zejia Li; Ziye Du; Rong Liu; Yi Li; Mengcheng Luo (Molecular Biology Reports, 2022)

Runoff projections of the Qinling Mountains and their impact on water demand of Guanzhong region in Northwest China - Zhao-peng Zhang; Ke-qin Duan; Huan-cai Liu; Ya-li Meng; Rong Chen; Da-wei Li; Shuang-shuang Li (Journal of Mountain Science, 2022)

Functional divergence of oligoadenylate synthetase 1 (OAS1) proteins in Tetrapods - Xiaoxue Wang; Jiaxiang Hu; Linfei Song; Enguang Rong; Chenghuai Yang; Xiaoyun Chen; Juan Pu; Honglei Sun; Chuze Gao; David W. Burt; Jinhua Liu; Ning Li; et al. (Science China Life Sciences, 2022)

MoS2 boosts the Fe2+/PMS process for carbamazepine degradation - Huan Peng; Rong Chen; Ningyao Tao; Yangyi Xiao; Chenxing Li; Tuqiao Zhang; Miaomiao Ye (Environmental Science and Pollution Research, 2022)

Selenium Deficiency Induces Autophagy in Chicken Bursa of Fabricius Through ChTLR4/MyD88/NF-κB Pathway - Ruili Zhang; Qing Liu; Rong Guo; Di Zhang; Yang Chen; Guangxing Li; Xiaodan Huang (Biological Trace Element Research, 2022)

Somatic embryogenesis in Rosa chinensis cv. ‘Old Blush’ - Yanfang Cai; Lintao Tang; Haixia Chen; Yufan Li; Rong Liu; Jiren Chen (Plant Cell, Tissue and Organ Culture (PCTOC), 2022)

Astragalus Polysaccharides Reduce High-glucose-induced Rat Aortic Endothelial Cell Senescence and Inflammasome Activation by Modulating the Mitochondrial Na+/Ca2+ Exchanger - Xin-Yu Miao; Xiao-Xiao Zhu; Zhao-Yan Gu; Bo Fu; Shao-Yuan Cui; Yuan Zu; Ling-Jun Rong; Fan Hu; Xiang-Mei Chen; Yan-Ping Gong; Chun-Lin Li (Cell Biochemistry and Biophysics, 2022)

Monascuslactams A–D, cytotoxic γ-lactams from marine fungus Monascus albidus BB3 - Qi Guo; Xiao-Ming Dai; Wen-Jian Lan; Liu-Ping Chen; Chi-Keung Lam; Gong-Kan Feng; Rong Deng; Xiao-Feng Zhu; Hou-Jin Li (Natural Product Research, 2022)

An IQ Consortium Perspective on Connecting Dissolution Methods to In Vivo Performance: Analysis of an Industrial Database and Case Studies to Propose a Workflow - Aktham Aburub; Yuan Chen; John Chung; Ping Gao; David Good; Simone Hansmann; Michael Hawley; Tycho Heimbach; Martin Hingle; Filippos Kesisoglou; Rong Li; John Rose; et al. (The AAPS Journal, 2022)

Ventromedial Thalamus-Projecting DCN Neurons Modulate Associative Sensorimotor Responses in Mice - Jie Zhang; Hao Chen; Li-Bin Zhang; Rong-Rong Li; Bin Wang; Qian-Hui Zhang; Liu-Xia Tong; Wei-Wei Zhang; Zhong-Xiang Yao; Bo Hu (Neuroscience Bulletin, 2022)

Identification and management of GCK-MODY complicating pregnancy in Chinese patients with gestational diabetes - Yanyan Jiang; Fusong Jiang; Ming Li; Qingkai Wu; Chenming Xu; Rong Zhang; Mingqiang Song; Yanzhong Wang; Ying Wang; Yating Chen; Juan Zhang; Xiaoxu Ge; et al. (Molecular and Cellular Biochemistry, 2022)

First report of Botryosphaeria dothidea causing leaf blotch of Mahonia bealei in China - Yi-Jia Cao; Rong-Han Chen; Yuan-Zhi Si; Li-Hua Zhu (Journal of Plant Pathology, 2022)

Flavonoid glycosides from the nectar of Camellia reticulata Lindl. - Xin-Lan Chen; Xing-Rong Peng; Xue-Yang Gong; Yi-Qiu Liu; Zhuo Qing; Xiao-Xiao Ren; Rui Su; Li-Ming Fang; Ming-Hua Qiu; Kun Dong (Natural Product Research, 2022)

Influence of Notch Geometry on the Rock Fracture Toughness Measurement Using the ISRM Suggested Semi-Circular Bend (SCB) Method - Geli Zhao; Wei Yao; Xing Li; Ying Xu; Kaiwen Xia; Rong Chen (Rock Mechanics and Rock Engineering, 2022)

A historical record of trace metal deposition in northeastern Qinghai-Tibetan Plateau for the last two centuries - Shanying Li; Weiwei Sun; Rong Chen; Zhijie Zhang; Dongliang Ning; Zhenyu Ni (Environmental Science and Pollution Research, 2022)

Monitoring the behavior of subway tunnels during early operation in saturated soft strata - Ben-Guo He; Rong-Li Zhen; Tian-Yu Chen; Hong-Pu Li (Bulletin of Engineering Geology and the Environment, 2022)

The establishment of giant panda (Ailuropoda melanoleuca) fibroblast cell line - Yuliang Liu; Jiasong Chen; Tongying Feng; Rong Hou; Zhigang Cai; Donghui Wang; Mingyue Zhang; Yuan Li; Yijiao Chen; Junhui An (In Vitro Cellular & Developmental Biology - Animal, 2022)

Sediment Resuspension as a Major Contributor to Sinking Particles in the Northwestern South China Sea: Evidence From Observations and Modeling - Lihua Ran; Wentao Ma; Martin G. Wiesner; Yuntao Wang; Jianfang Chen; Lanlan Zhang; Zhi Yang; Jingjing Zhang; Hongliang Li; Jian Ren; Rong Xiang; Erick Fredj (Frontiers in Marine Science, 2022)
The lateral advection of sinking particles is a well-known phenomenon in the South China Sea (SCS) and has a significant impact on the estimation of the efficiency of the biological carbon pump. However, little is known about the sources and pathways of sinking particles. Here, we present benthic and freshwater diatom fluxes and relative abundances collected by a sediment trap deployed at a water depth of 1,000 m and more than 500 m above the seafloor in the northwestern SCS, indicating that laterally transported resuspended sediment accounts for a significant part of the particle flux to the deep sea. A Lagrangian particle tracking model (LPTM) revealed that the resuspended particles likely originated from the neighboring continental slope, approximately 12–145 km to the west of the study site. Sediment trap observations and the LPTM together indicated that the impact of resuspended sediment occurred mainly in the deep water, and especially strong sediment resuspension was related to summer monsoon-induced coastal upwelling. The results suggest that particle resuspension has an important impact on the biological pump as well as on paleoenvironmental reconstructions of the SCS.

Neoflavonoids from the heartwood of Dalbergia melanoxylon - Meng-fei Wang; Guang-qiang Ma; Feng Shao; Rong-hua Liu; Lan-ying Chen; Yang Liu; Li Yang; Xiao-wei Meng (Natural Product Research, 2022)

Does the institutional environment influence corporate social responsibility? Consideration of green investment of enterprises—evidence from China - Shu-Rong Han; Pei Li; Jian-Jun Xiang; Xiang-Hua Luo; Chun-Yan Chen (Environmental Science and Pollution Research, 2022)

Selenium Deficiency Causes Inflammatory Injury in the Bursa of Fabricius of Broiler Chickens by Activating the Toll-like Receptor Signaling Pathway - Yu Bai; Ruili Zhang; Qing Liu; Rong Guo; Guangxing Li; Bin Sun; Di Zhang; Yang Chen; Xiaodan Huang (Biological Trace Element Research, 2022)

Eutrophication and predation mediate zooplankton diversity and network structure - Yun Li; Rong Wang; Haojie Su; Jianjun Wang; Ping Xie; Feizhou Chen (Limnology and Oceanography, 2022)
Anthropogenic activities such as eutrophication and fishing have prominent effects on freshwater ecosystems. However, the ways in which ecosystem function and biodiversity respond to multiple drivers from eutrophication and top‐down predation remains inconclusive. We studied zooplankton communities in 102 subtropical shallow lakes in the eastern plain of China and further examined the joint effects of nutrient enrichment and predation on biodiversity and ecological networks. We found that alpha diversity was negatively influenced by nutrient conditions (such as total phosphorus and total nitrogen [TN]), whereas beta diversity (β‐diversity) was positively related to nutrients and was also structured by omnivorous fish showing a unimodal pattern. Furthermore, the network skewness of zooplankton increased with nutrient enrichment, especially TN, and was negatively related to omnivorous fish. This skewness is more sensitive than β‐diversity, whereas negative skew is primarily caused by omnivorous fish. Our results demonstrated that top‐down effects were dominant for zooplankton communities and resulted in structural adjustment of zooplankton communities, mainly with an increase in fish predation. A negative skewed network indicates the presence of more generalist species and stronger connections among the zooplankton assemblages, as well as decreased β‐diversity.